Mapping Human Capital Readiness for Digital Transformation in Disaster-Prone Regions: Evidence from West Sumatra - Farlis, Fiko; Rachmat Riski, Tri; Setyo Aguindra, Bintang (AMAR (Andalas Management Review), 2025)
This study analyzes the distribution of the Human Capital Readiness Index (HCRI) among workers in disaster-prone areas of West Sumatra, focusing on Padang City and Pesisir Selatan Regency. The index, constructed through a Principal Component Analysis (PCA) of four dimensions digital competence, adaptability, information access, and sustainability planning—illustrates the workforce’s readiness for post-disaster digital transformation. Based on responses from 384 workers, results show that 50.52% fall into the High Readiness category, 25.78% Moderate, 16.41% Very High, 6.77% Low, and only 0.52% Very Low. These findings indicate that most workers demonstrate a relatively strong readiness level, supported by increasing digital exposure and adaptive capacity, yet gaps remain in planning and information access. The results highlight the importance of targeted human capital interventions and digital capacity development to ensure equitable resilience across both formal and informal sectors in disaster-affected regions